IMPLEMENTASI KEGIATAN PEMBERDAYAAN MASYARAKAT DALAM KEBIJAKAN DESA WISATA DI KELURAHAN KANDRI KECAMATAN GUNUNGPATI KOTA SEMARANG - Yohanes R. Juanda; Amni Zarkasyi Rahman (Journal of Public Policy and Management Review, 2016)
Community empowerment activities is one of the key components as an effort to overcome the problems of underdeveloped Kandri administrative village area as a tourism village in the city of Semarang. It is important considering the majority livelihoods of Kandri villagers are working on the agricultural sector, then to transform to involve in the field of tourism business. This research will further elaborate the implementation of community empowerment activities in the policy of tourism village in Kandri administrative village, Gunungpati district, city of Semarang. The method used in this research is qualitative - descriptive type, with key informants from the staff of Semarang Municipal Office of Cultural and Tourism that specifically managed programs related with tourism village, and community members of Kandri administrative village part of the Kelompok Sadar Wisata (Pokdarwis) management. The purpose of this study is to analyze the implementation of community empowerment activities from the 5 accuracy theory by Riant Nugroho, and describing factors influencing the implementation of activities. The results of the research shown that in the implementation of the undertaken activities, there are problems related to the suitability of the activities provided to local conditions; the assigned of target community; and the transformation process of the local community to become businessmen in tourism sector. Constraint factors of the community empowerment implementation process are the clarity and policy standards, the commitment of governments, social and economic conditions, and the disposition of the implementor. Recommendation earned from this research are : increasing participation of the Tourism Department in the development of Kelompok Sadar Wisata (Pokdarwis) on Kandri administrative village, proportionally to both Pokdarwis Pandanaran and Pokdarwis Sukomakmur; guidelines for the implementation were made by The Government toward the undertaken activities; and clear budget allocation in supporting the activities.